Poważny brak rozeznania oceniającego (kan. 1095, n. 2 KPK) w wyroku Roty Rzymskiej c. Salvatori z 7 maja 2020 roku - Góralski, Wojciech (Ius Matrimoniale, 2019)
The negative sentence c. Salvatori in the case under the gravis defectus discretionis iudicii (can. 1095, n. 2 CIC) on both sides, taken in the second instance, when the first ruled positively in relation to both parties, is an example of a reliable assessment of the collected material evidence. In the sentence, quite a lot of space was devoted to the role and tasks of an expert in the cases of can. 1095, n. 1-3 CIC. It is worth emphasizing here that an opinion prepared solely on the basis of the case file is not a true expert opinion. Salvatori pointed to the practice developed in rotational jurisprudence, according to which a judge should reject an expert’s conclusions when they do not comply with the case files or violate the rules of logic or go beyond the premises on which they are based, or when they are inconsistent with Christian anthropology. Ponens convincingly demonstrated the groundlessness of prof. D. (with respect to the woman) grossly inconsistent with the case files and going far beyond the premises that served him to formulate such a thesis.